CARE: Marikina city proto-type evacuation center, Marikina Height, Marikina City - Acosta, Julie Ann L. (Manila : National University, 2016)
Marikina City was known for its remarkable shoe industry in the whole country and was recognized by the other countries. Despite of this the city faces serious calamity disturbances. It is one of the most affected areas in Metro, Manila when it comes to calamity. Its vulnerability to hazards such as floods, earthquakes and landslides took a lot of damage to property and lives of the people. The tendency of the calamities causes a lot of the residents to evacuate this lead to the congestion and improper sanitation of the designated evacuation areas allotted by the government. This study explores the needs to have a safer and comfortable temporary shelter in times of calamity. This lead to the aim of having Proto-type Evacuation center which will serve as temporary shelter in times of calamity and will also function multi-purposely and flexibly that can be collapsible and transported. The structure that has adaptation to climate was to be studied and analyzed. The economic aspect was also considered to suit the budget of the government. Climatic condition of the city was also presented and analyzed; the data gathered were taken from the officials in charged. To support the study standards and guidelines in designing evacuation center were used through interviews and researches.
Acknowledgment -- Certificate of endorsement -- Approval sheet -- List of tables -- List of figures -- List of graphs -- Abstract -- 1. Problem & its setting -- 2. Research methodology 3. Terms and reference -- 4. Data gathering, collation & analysis of data -- 5. Design framework -- 6. Schematic translations -- Bibliography -- Appendices.
Research design: Descriptive method